Nessus network auditing - Rogers, Russ; Carey, Mark S.; Criscuolo, Paul; Petruzzi, Mike (Syngress, 2008)
The first edition of Nessus sold just under 10,000 units worldwide.
Includes bibliographical references and index. - Print version record
Keywords: Computer networks; Computer Communication Networks; Réseaux d'ordinateurs; COMPUTERS; Networking; Vendor Specific; COMPUTERS; Data Transmission Systems; General